2016
DOI: 10.1049/htl.2016.0006
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability estimation in photoplethysmography signals using Bayesian learning approach

Abstract: Heart rate variability (HRV) has become a marker for various health and disease conditions. Photoplethysmography (PPG) sensors integrated in wearable devices such as smart watches and phones are widely used to measure heart activities. HRV requires accurate estimation of time interval between consecutive peaks in the PPG signal. However, PPG signal is very sensitive to motion artefact which may lead to poor HRV estimation if false peaks are detected. In this Letter, the authors propose a probabilistic approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…In addition to activity intensity, several other studies have identified that motion artifacts during exercise were negatively correlated with the accuracy of PPG heart rate-monitoring systems [32,38,46,[54][55][56]. For example, in an experiment conducted by Gillinov et al [2], the optical devices exhibited more accuracy for exercise with fewer arm motion artifacts (cycling and elliptical exercise with no arms movement).…”
Section: Principal Findingsmentioning
confidence: 99%
“…In addition to activity intensity, several other studies have identified that motion artifacts during exercise were negatively correlated with the accuracy of PPG heart rate-monitoring systems [32,38,46,[54][55][56]. For example, in an experiment conducted by Gillinov et al [2], the optical devices exhibited more accuracy for exercise with fewer arm motion artifacts (cycling and elliptical exercise with no arms movement).…”
Section: Principal Findingsmentioning
confidence: 99%
“…However, the complicated operations made the algorithm not suitable for wearable systems. In the time domain, the AMPD-BL algorithm in [29], jointly integrating the AMPD [15] and Bayesian learning (BL) approaches, was used to estimate the heart rate data.…”
Section: Time-frequency Analysismentioning
confidence: 99%
“…Multi-peak detection is a type of algorithm that can find multiple local optimal points, [12][13][14][15][16] and automatic multiscale-based peak detection (AMPD) 17,18 and Fibonacci peak detection (FPD) 19 are such a multi-peak detection algorithm. [17][18][19][20][21][22] In applications, however, optimization performances and computational complexity of the multi-peak detection algorithms often depend on the parameters such as search range, search depth, and the number of sprinkling. Inappropriate parameter settings often lead to slow convergence of algorithms, failure to find extreme values.…”
Section: Related Workmentioning
confidence: 99%